(untitled) - Mal, Bidyut (Darya Ganj, New Delhi, 2004)
Contents of material: 1/ Documentation of electronic texts. 2/ Documentation and archival collections. 3/ Library collection management. 4/ Methods of modern libraties. 5/ Changing trends of librarianship. 6/ Challenges of libraries.
Keywords: Library science,Information technology